THE THE CORRELATION BETWEEN FLAT FOOT WITH STATIC AND DYNAMIC BALANCE IN ELEMENTARY SCHOOL CHILDREN 4 TONJA DENPASAR CITY - Antara, Kadek Ady; Adiputra, I Nyoman; Sugiritama, I Wayan (Majalah Ilmiah Fisioterapi Indonesia, 2018)
ABSTRACT The development of balance during child growth is very important to be reviewed. Deformity of the sole of the foot is one of the causes of disturbance of balance. This research is analytic with cross sectional approach. In 101 samples (58 male samples, 43 female samples), age 6-11 years, the measured independent variable was flat foot through the wet footprint test. The dependent variables measured were static balance through standing stork test, and dynamic balance through Balance beam test. In Spearman's rho data analysis calculation known value of significance (2- tailed) is 0,000 for static and dynamic balance, which means significance value <?. Furthermore, it is known Correlation Coefficient (correlation coefficient) of 0.933 for static balance, and 0.828 for dynamic equilibrium. Based on the data output, it can be concluded that there is a strong, significant, and unidirectional relationship between the flat foot with static and dynamic balance in the 4th school elementary school of the 4th city of Denpasar. Keywords: Flat Foot, Static Balance, Dynamic Balance